Bending analysis and residual stress measurement of thin stainless-steel alloy. (2022) - Ganesh Kumar, S.; Bharath Kumar, S.; Praveenkumar, K.; Swaroop, S.
Abstract: LPF (laser peen forming) is a non-contact sheet metal forming technology that uses a laser detonated shockwave to bend, shape, and fix engineering components accurately. To understand the bending behavior of SS-304 steel samples in the form of thin sheets of various thicknesses (0.3, 0.5, and 0.8 mm), laser peening at various power densities (3, 6, and 9 GW /cm 2 ) was used. After the peening process, laser peened samples show convex and concave bending. The bending that occurs as a result of residual stress distribution across the sample's cross section during the laser peening process. As a result, to better understand the role of residual stress in LPF, the residual stress was studied using the usual X-ray based cos approach. The significance of these findings for a possible laser forming process known as laser peen forming are also investigated.